FORMATION OF SOCIAL CONSCIOUSNESS IN OLDER PRESCHOOL CHILDREN - Shoista Sadikova; Dildora Azamatova (European Science Publishing, 2024)
The article talks about the skills of forming social consciousness in preschool children.
Keywords: preschool education, child, social consciousness, pedagogy.